URGENSI PERLINDUNGAN HUKUM TERHADAP JUSTICE COLABORATOR DALAM TINDAK PIDANA KORUPSI: - - Silitonga, Dony Andrianto; Jamba, Padrisan (SCIENTIA JOURNAL, 2023)
Criminal acts, such as corruption, are illegal actions committed by individuals that harm the state for personalor others' benefits. Corruption is considered an exceptional crime, making investigations challenging due tothe intricate methods employed by the perpetrators. This difficulty led to the introduction of the term "perpetratorwitness" or "justice collaborator," referring to a witness who cooperates with law enforcement authorities toinvestigate the same crime. The objective of this study is to examine the legal arrangements and protectionmeasures afforded to justice collaborators in sharing information. The research employed a normative legalresearch method, utilizing library research and primary, secondary, and tertiary data sources. The findingsreveal several legal provisions, including Law No. 31 of 2014 and SEMA No. 4 of 2011, as well as forms ofprotection provided by law enforcement agencies, encompassing physical and psychological safeguards.However, it can be inferred from the study that the legal foundation for justice collaborators lacks clarity, as itholds the potential for multiple interpretations in practical implementation. Additionally, the level of protectionprovided and the fulfillment of promises by law enforcers have not been fully optimized